2019
DOI: 10.1097/brs.0000000000003364
|View full text |Cite
|
Sign up to set email alerts
|

Should Thoracolumbar Junction Be Always Avoided as Upper Instrumented Vertebra in Long Instrumented Fusion for Adult Spinal Deformity?

Abstract: Study Design. Retrospective study. Objective. The aim of this study was to investigate the risk factors for proximal junctional failure (PJF) following long instrumented fusion stopping at thoracolumbar junction (TLJ) in adult spinal deformity (ASD) and to determine which cases are suitable for TLJ stop without increasing the risk for PJF. Summary of Background Data. PJF following long fusion for ASD is a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…The risk factors for rod breakage are elderly patients, worse ASA score, obesity, long segment fusions, three-column osteotomy, the high sagittal vertical axis (SVA), thoracic kyphosis, over-correction, and sagittal malalignment. [ 44 57 59 61 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors for rod breakage are elderly patients, worse ASA score, obesity, long segment fusions, three-column osteotomy, the high sagittal vertical axis (SVA), thoracic kyphosis, over-correction, and sagittal malalignment. [ 44 57 59 61 ]…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a risk factor for instrumentation failure. [ 61 ] Screening tests for osteoporosis for elderly patients should be done routinely. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although the main consensus in the literature agreed that UIV and UIV + 1 fractures that occurred after long instrumented fusion were classified as PJF [ 2 , 3 , 11 , 12 , 22 ], there were similarities and differences in radiographic and clinical features between these two groups. According to the present study, the patients in both groups were osteoporotic as defined by their BMD, had same age and similar BMI/ASA scores/CCI at index surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yagi et al observed 113 patients underwent surgical correction for their adult spinal deformities by method of propensity-matched comparison and concluded that low bone-mineral density is a signi cant risk factor to develop PJF [13]. Park et al studied 63 cases underwent posterior instrumented fusion with their UIV at thoracolumbar junction and concluded that older than 70 years old and osteoporosis would increase incidence of PJF [14]. Because primary osteoporosis is positively related to age, it is easy to understand that patient with older age had higher incidence to develop PJF.…”
Section: Discussionmentioning
confidence: 99%